On the contribution of binocular disparity to the long-term memory for natural scenes - Valsecchi, Matteo; Gegenfurtner, Karl R.; Justus Liebig University Giessen (My University, 2012)
Binocular disparity is a fundamental dimension defining the input we receive from the visual world, along with luminance and chromaticity. In a memory task involving images of natural scenes we investigate whether binocular disparity enhances long-term visual memory. We found that forest images studied in the presence of disparity for relatively long times (7s) were remembered better as compared to 2D presentation. This enhancement was not evident for other categories of pictures, such as images containing cars and houses, which are mostly identified by the presence of distinctive artifacts rather than by their spatial layout. Evidence from a further experiment indicates that observers do not retain a trace of stereo presentation in long-term memory.
Keywords: binocular disparity; long-term visual memory; natural scenes; stereo presentation; ddc:150